(untitled) (Conference Zone, 2022)
The main goal of inclusion as a process is to create a barrier-free environment for the education and training of people with special needs. One of the aspects of the development of inclusive education is pedagogical work with children with learning difficulties such as mental difficulties. Another aspect of the development of inclusive education is the training of specialists to accompany students of this group.